Peranan medan magnet dan campuran etanol-biodiesel minyak jelantah pada pembakaran droplet terhadap perilaku api dan emisi gas buang - Perdana, D.; Fiyanto, S.F.W.A. (Universitas Mataram, 2024)
Petroleum reserves are increasingly depleting, causing a scarcity of petroleum fuel caused by the rapid progress of transportation and the manufacturing industry. This condition forces researchers to search for and develop new renewable energy source. The purpose of research is to understanding and determines role of north-south (U-S) and south-south (S-S) magnetic fields to blend waste cooking oil biodiesel-ethanol on flame evolution, flue gas emissions, and temperature during droplet combustion. Waste cooking oil biodiesel and ethanol were used in this research by adding variations in the direction of repulsive and attractive magnetic fields with an intensity of 11000 gauss. Diameter of droplets tested was 0.3 mm and was placed on a type K thermocouple wire with diameter of 0.1 mm. This research found the role of attractive magnetic field (U-S) in blend waste cooking oil biodiesel-ethanol 20% to produce the shortest flame evolution of 704 ms, lowest CO of 165 ppm, and highest temperature of 828.5 oC. This happens because ethanol has a low flash point and large oxygen content, causing the combustion reaction to occur rapidly. The attractive of magnetic field (U-S) plays a role on attracting oxygen around flame to enter combustion reaction, while the H2O resulting from combustion is pumped out of flame.